Low-back related leg pain: is the nerve guilty? How to differentiate the underlying pain mechanism. (4th March 2023) - Fourré, Antoine; Monnier, Félix; Ris, Laurence; Telliez, Frédéric; Michielsen, Jef; Roussel, Nathalie; Hage, Renaud
ABSTRACT: Low back pain (LBP) that radiates to the leg is not always related to a lesion or a disease of the nervous system (neuropathic pain): it might be nociceptive (referred) pain. Unfortunately, patients with low-back related leg pain are often given a variety of diagnoses (e.g. 'sciatica'; 'radicular pain'; pseudoradicular pain"). This terminology causes confusion and challenges clinical reasoning. It is essential for clinicians to understand and recognize predominant pain mechanisms. This paper describes pain mechanisms related to low back-related leg pain and helps differentiate these mechanisms in practice using clinical based scenarios. We illustrate this by using two clinical scenarios including patients with the same symptoms in terms of pain localization (i.e. low-back related leg pain) but with different underlying pain mechanisms (i.e. nociceptive versus neuropathic pain).